Legal personality of legal entities: some problematic aspects - Yu. I. Chalyi (Law and Safety)
The concepts and elements of legal personality of legal entities are defined. This research emphasis is explained by the fact that legal entities do not have a bodily substrate. Recognition of the participation of legal entities in civil legal relations is through the external realization of the legal personality of these persons. This circumstance explains the urgency of addressing the issues of legal personality of legal entities. The category of "legal personality", when disclosed in the context of defining the subjectivity of legal entities, can be understood in two senses: 1) as a legal consequence of an act of legislation (in the form of state registration), which entails the recognition of the qualities of the subject by a certain organization or, that is, the recognition by the organization of the status of "legal entity"; 2) as a detailed description of the qualities of the subject, indicating not only his legal ability to have rights and responsibilities in the future (legal capacity), but also the ability to independently form the will and express it externally by implementing legally significant acts of conduct (capacity). The application of the formal-legal (dogmatic) method made it possible to conclude that the elements of legal personality of legal entities should be recognized as legal capacity and legal capacity. Legal capacity determines the legal existence of legal entities and indicates the extent of their participation in civil or other legal relations. It is argued that the legal capacity of legal entities is incorrect to determine through the categories of "general (universal)" or, conversely, "special (target)". It is emphasized that the functional purpose of the legal capacity of legal entities is not to determine the limits of their active legal personality, as in the case of the legal capacity of individuals, but to establish the range of persons (bodies, officials, participants), by the will and expression of which the subjective legal potential of legal entities can be realized.